Computer‐Aided Discovery of Trypanosoma brucei RNA‐Editing Terminal Uridylyl Transferase 2 Inhibitors. (5th June 2014) - Demir, Özlem; Labaied, Mehdi; Merritt, Chris; Stuart, Ken; Amaro, Rommie E.
<x xml:space="preserve">Abstract</x> Human African trypanosomiasis (HAT) is a major health problem in sub‐Saharan Africa caused by Trypanosoma brucei infection. Current HAT drugs are difficult to administer and not effective against all parasite species at different stages of the disease which indicates an unmet pharmaceutical need. TbRET2 is an indispensable enzyme for the parasite and is targeted here using a computational approach that combines molecular dynamics simulations and virtual screening. The compounds prioritized are then tested in T. brucei via Alamar blue cell viability assays. This work identified 20 drug‐like compounds which are candidates for further testing in the drug discovery process.